Effects of organic manures and bio-fertilizers on growth, flowering and yield of China aster (Callistephus chinensis L. Nees var. Kamini) - Marak, Bidanchi S; Kumar, Sunil; Momin, Kalkame CH (Bangladesh Journal of Botany, 2020)
Effects of organic manures and bio-fertilizers on growth, flowering and yield of China aster (Callistephus chinensis) var. kamini was investigated. The experiment with 12 treatment combinations comprising of FYM, vermicompost and bio-fertilizers viz., phosphate solublising bacteria (PSB) and Azospirillum was conducted. All the treatment combinations showed significant response in vegetative, flowering and yield characters during the entire investigation. The treatment combinations of Azospirillum + PSB + vermicompost + 50% RDF was found to be promising for maximum plant height (63.97 cm), plant spread (21.50 cm), stem girth (15.47 mm), number of primary branches per plants (12.33), number of secondary branches per plants (22.14), enhanced flower bud emergence (73.33 days), stalk length (32.20 cm), number of flowers per plant (24.35), flower diameter (46.18 mm), prolonged flower duration (23.05 days), flower yield (18.87 q/ha) and seed yield (2.44 q/ha) were on par with Azospirillum + PSB + FYM + 50% RDF.